Chronotopes of Flight from the Red Army in East and West German Feature Film (1950–1970) - Jamie Zelechowski (Studies in 20th & 21st Century Literature, 2019)
This article investigates the representation of flight from the Red Army (1944/45) in East and West German feature film prior to 1970. Even while refugee figures may abound, the representation of flight appears infrequently in feature film during this period. In order to understand why this is the case as well as how and why flight is actually depicted when it is, I turn to Wolfgang Schleif’s Preis der Nationen/Das Mädchen Marion (Prize of the Nations/The Girl Marion, FRG; 1956) and Martin Eckermann’s television film Wege übers Land (Ways Across the Land, GDR; 1968) and their representations of refugee treks—which, like the other films in this corpus, draw on archival footage and photographs for their own compositions. I consider the refugee trek as a specific subset of what Mikhail Bakhtin calls the “chronotope of the road” and analyze the intersection of the chronotope of the road (of flight) with the photographic index. It is at this intersection that the films negotiate between the competing myths, politics, and collective memories that saturated the socially and politically volatile issue of flight and the ‘lost German East’. What my analysis shows is that cinematic stagings of flight from the Red Army such as those in Preis der Nationen and Wege übers Land challenge, re-frame, or re-purpose the icons of flight in order to diffuse irredentist political messages and to demonstrate the successful integration of Flüchtlinge/Vertriebene ‘refugees/expellees’ and Umsiedler ‘resettlers’ into West and East Germany, according to each state’s respective foundational narrative.
Keywords: flight and expulsion; German film; chronotope; refugees